IMPLEMENTASI GAGASAN HASAN AL-BANNA TENTANG PENDIDIKAN AKHLAK DALAM SISTEM PENDIDIKAN NASIONAL - Muktar, Muktar (Universitas Islam Negeri Sumatera Utara Medan, 2024)
Hasan Al-Banna was one of the Islamic reformers of the 20th century who paid great attention to moral education as the main foundation for community development. This article aims to examine Hasan Al-Banna's ideas on moral education and evaluate the possibility of their implementation in the Indonesian national education system. The method used in this study is library research with a qualitative-descriptive approach. The results of the study indicate that Hasan Al-Banna's thinking places moral education at the core of education, which must be integrated with the formation of faith, intellectuality, and social life. Some of the principles he promotes include the integration of knowledge and practice, education based on role models, and the role of family and society in the educational process. This article recommends the integration of these moral values into the national curriculum in a transdisciplinary manner through an approach based on religiosity and role models.